Effect of Exports of Goods and Services and Energy Consumption in Italy`s Service Sector - Huseynli, Bahman (International Journal of Energy Economics and Policy, 2023)
The aim of this study is to examine the service sector in Italy, one of the Mediterranean countries, and the relationship between the energy consumption affecting this sector and the factors of export of goods and services. The data set used in the model tested by panel analysis method covers the years 1997-2021. When the values related to the analysis result are examined, it is understood that the model is generally significant at the 95% confidence level. The R2 coefficient, which is important in the model, is approximately 95%. Exports of goods and services, one of the explanatory variables in the model, were found to be significant in explaining the commercial service exports of this country. In other words, the 1% increase in Italy’s exports of goods and services explains this country’s exports of commercial services at the level of 86%. This relationship between variables has a positive meaning. The relationship between energy consumption and exports of commercial services was found to be significant at the 5% probability level. The relationship between these two variables is also positive. It was concluded that a 1% increase in energy consumption explains this country’s commercial service exports by approximately 27%.